Pareto-optimal analysis of adverse drug reactions induced by Chinese patent medicine and clinical medication management - Meihong CHEN; Fei TONG; Linqian GUO; Jingming LIN; Zhaoyu WANG (KeAi Communications Co., Ltd., 2021)
[Abstract]: Objective: To provide the optimal measure for the prevention and control of adverse drug reactions (ADRs) of Chinese patent medicine (CPM), high-risk factors of ADRs induced by CPM were explored. Methods: ADR report data of CPM from patients hospitalized in a Level III Grade A Hospital for 7 consecutive years were collected, and Pareto-optimal analysis method was used to determine the high-risk characteristic values of patients' age, drug type, and involved systems/organs. Results: The high-risk characteristics for ADRs included age ≥ 51 years, blood-regulating drugs, and ADRs were observed most commonly in systemic damage, damage in the cardiovascular system, and skin and its accessories. Conclusion: These high-risk characteristics should be considered when prescribing CPM. Drugs and medical instruments required for ADR treatment should be prepared before drug use, and early symptoms of ADRs should be monitored closely during CPM administration to timely discontinue suspected drugs, provide appropriate treatment, and improve prevention and control of ADRs.